First description of buckler crab Cryptopodia angulata (H. Milne Edwards and Lucas 1841) from Bangladesh marine water - Sharifuzzaman, SM; Chowdhury, Sayedur Rahman; Sadek, Md Abu; Fuad, Md Tariful Islam; Hossain, M Shahadat (Bangladesh Journal of Zoology, 2018)
Abstract not available Bangladesh J. Zool. 46(2): 275-280, 2018